Perfil epidemiológico dos acidentes ofídicos na mesorregião do Triângulo Mineiro e Alto Paranaíba - Santos, Gustavo Mendes dos (2023)
Introduction: Snakebite or snakebite is defined as an accident caused by snakes through venom. Poisoning only happens when venom from the snake's venomous glands is injected into the victim. It is estimated that there are more than 3000 species of snakes in the world, 400 of which are recognized as venomous. Snakebite are a concern for thousands of people in different regions of the world. The World Health Organization (WHO) states that accidents caused by poisonous snake bites are one of the most neglected public health problems affecting the regions where these animals live. In 2017, the WHO classified snakebite as a category A Neglected Tropical Disease, this is the highest of the categories used to classify these diseases. Objective: To characterize the epidemiological profile of snakebites in the Triângulo Mineiro and Alto Paranaíba mesoregion of the state of Minas Gerais in the period from 2012 to 2021. Material and Methods: This is a cross-sectional study, with secondary data and public access, carried out in the mesoregion of Triângulo Mineiro and Alto Paranaíba. The study variables were: year, microregion of residence, age group, sex, work accident, race/color, education, type of snake, time between bite and care, case classification, final evolution, month of occurrence and location of the bite. On the SINAN-DATASUS-TABNET platform, microregions were allocated and the other available variables were selected. The data were subjected to statistical analysis using the JAMOVI 2.3.21 program. Results: 3,868 cases of snakebites were recorded during the study period and mesoregion. The months from October to April were those with the highest occurrence, with emphasis on the month of March, which accounted for 12.5%. The age groups from 20 to 39 and from 40 to 59 remained above the expected proportion, together totaling almost 0.700 proportion. Males stood out with a proportion of 0.778. Regarding whether it was a work accident or not, the proportion was 0.685 for the answer “no”. White race/color stands out, which totaled 0.5285. Most victims had 5 to 8 years of schooling (0.3956). The feet and legs were the most affected areas during accidents in different age groups. The largest number of accidents was caused by the genus Bothrops, of jararacas. The time elapsed between the bite and care, from 0 to 1 hour, was the one with the highest value. Mild cases had a higher proportion (0.482). Conclusion: Snakebites are an important public health problem in the Triângulo Mineiro and Alto Paranaíba. The male population, in economically active age groups and with low education, are those most affected by the disease.